2006
DOI: 10.1524/ract.2006.94.5.239
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the thermal release of iodine from liquid eutectic lead-bismuth alloy

Abstract: SummaryThe release of iodine from liquid eutectic lead-bismuth alloy (LBE) under a flowing Ar/7%H

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Iodine is commonly believed to be well retained in lead alloy coolants [3]. To verify this claim, we have characterized iodine evaporation from dilute solution in LBE by the so-called transpiration method and confirmed, consistent with experiments at much lower concentrations using a different source of iodine [19], that iodine evaporation from LBE is indeed strongly suppressed compared to evaporation of pure iodine.…”
Section: Fission and Spallation Product Chemistry And Evaporationsupporting
confidence: 59%
“…Iodine is commonly believed to be well retained in lead alloy coolants [3]. To verify this claim, we have characterized iodine evaporation from dilute solution in LBE by the so-called transpiration method and confirmed, consistent with experiments at much lower concentrations using a different source of iodine [19], that iodine evaporation from LBE is indeed strongly suppressed compared to evaporation of pure iodine.…”
Section: Fission and Spallation Product Chemistry And Evaporationsupporting
confidence: 59%
“…Furthermore, also in the exhaust gas monitoring no large quantities of iodine isotopes were found [10]. Finally, in dedicated experiments on the evaporation of iodine from LBE [21] it was shown that significant evaporation occurs only at temperatures >500 ∘ C, much a Average of two calculations using different nuclear models. higher than the temperatures of the LBE free surface in the MEGAPIE target during operation (approx.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been performed on the evaporation of iodine from a dilute solution in LBE in an inert (Ar/5%H 2 ) atmosphere. One of the studies found significant volatilization occurring around 800 K in an inert atmosphere (Ar/5%H 2 ) [2], however another found release temperatures around 700 K [3]. The maximum coolant temperature of the MYRRHA is 723 K [4], so fractional evaporation of iodine is expected which merits studying it in more detail.…”
Section: Introductionmentioning
confidence: 99%